A SYSTEMATIC REVIEW AND META-ANALYSIS: RISK FACTORS OF MORTALITY COVID-19: Sistematik Review dan Meta-Analisis: Faktor Risiko Kematian COVID-19 - Febrianti, Thresya; Falmuriat, Qurratu (Jurnal Berkala Epidemiologi, 2024)
Background: COVID-19 is still a threat throughout the world because of its high morbidity and mortality. Comorbid diseases like hypertension, diabetes mellitus, and heart disease are some of the factors in the high severity and mortality of COVID-19 patients. Purpose: The study aims to analyze the effect of risk factors on COVID-19 mortality using a systematic review and meta-analysis. Methods: Articles were taken from online journal portals Pubmed, Garuda, and Google Cendekia, and all were published from October 2019 to December 2021 in full text and with an observational study design. The keywords used in searching the articles were "COVID-19", "sars cov 2", "2019-nCoV", "2019 novel coronavirus", "COVID-19 deaths", and "COVID-19 mortality". The articles were collected using a PRISMA diagram; then, data extraction was carried out in a systematic review. The data was synthesized by using a meta-analysis technique using the RevMan application. Results: This study analyzed 59 articles and found that age, hypertension OR=3.09 (2.69-3.56), sex OR= 1.29 (1.08-1.53), and diabetes mellitus OR=3.03 (2.66-3.44) are the risk factors for COVID-19 death. Conclusion: The death in COVID-19 patients is influenced by elderly age, gender, and comorbid disease (diabetes and hypertension). These COVID-19-death-related factors can help health workers recognize and prevent a more severe stage of the disease through more appropriate handling and treatment.